Retinal Image Enhancement Using Cycle-Constraint Adversarial Network - Wan, Cheng; Zhou, Xueting; You, Qijing; Sun, Jing; Shen, Jianxin; Zhu, Shaojun; Jiang, Qin; Yang, Weihua (Frontiers in Medicine, 2022)
Retinal images are the most intuitive medical images for the diagnosis of fundus diseases. Low-quality retinal images cause difficulties in computer-aided diagnosis systems and the clinical diagnosis of ophthalmologists. The high quality of retinal images is an important basis of precision medicine in ophthalmology. In this study, we propose a retinal image enhancement method based on deep learning to enhance multiple low-quality retinal images. A generative adversarial network is employed to build a symmetrical network, and a convolutional block attention module is introduced to improve the feature extraction capability. The retinal images in our dataset are sorted into two sets according to their quality: low or high quality. Generators and discriminators alternately learn the features of low/high quality retinal images without the need for paired images. We analyze the proposed method both qualitatively and quantitatively on public datasets and a private dataset. The study results demonstrate that the proposed method is superior to other advanced algorithms, especially in enhancing color-distorted retinal images. It also performs well in the task of retinal vessel segmentation. The proposed network effectively enhances low-quality retinal images, aiding ophthalmologists and enabling computer-aided diagnosis in pathological analysis. Our method enhance multiple types of low-quality retinal images using a deep learning network.